2011
DOI: 10.1084/jem.20100900
|View full text |Cite|
|
Sign up to set email alerts
|

Local microbleeding facilitates IL-6– and IL-17–dependent arthritis in the absence of tissue antigen recognition by activated T cells

Abstract: Local microbleeding induces the accumulation of Th17 cells and the development of IL-17– and IL-6–dependent arthritis in the absence of cognate antigen recognition by CD4+ T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 70 publications
3
84
0
Order By: Relevance
“…In addition, although we saw similar levels of IL-17 in LN and spleens of mice with CIA whether or not they were transferred with the HCF4Vβ7 line, more IL-17–producing HCF4Vβ7 + cells were present in the synovium of mice with CIA, indicating a local effect of the cells in an already inflamed environment. An alternative explanation for enhanced arthritis in this study is that HCF4Vβ7 + CD4 T cells act as a local source of IL-17 in the joint, as reported previously (61). However, in our studies, OVA-specific CD4 T cells also produced IL-17 in response to OVA and trafficked to spleens, LN, and synovium when transferred into mice with CIA, but arthritis was not increased in these animals.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, although we saw similar levels of IL-17 in LN and spleens of mice with CIA whether or not they were transferred with the HCF4Vβ7 line, more IL-17–producing HCF4Vβ7 + cells were present in the synovium of mice with CIA, indicating a local effect of the cells in an already inflamed environment. An alternative explanation for enhanced arthritis in this study is that HCF4Vβ7 + CD4 T cells act as a local source of IL-17 in the joint, as reported previously (61). However, in our studies, OVA-specific CD4 T cells also produced IL-17 in response to OVA and trafficked to spleens, LN, and synovium when transferred into mice with CIA, but arthritis was not increased in these animals.…”
Section: Discussionsupporting
confidence: 68%
“…A process of “epitope spreading” has been described in a number of autoimmune settings (45), and it is possible that IL-17-secreting 6.5 − CD4 + T cells cause disease because they utilize endogenous TCRs that recognize joint-specific self-peptides, including cryptic self-peptides that might be presented by unconventional APCs such as synoviocytes that become MHC class II-positive in the inflamed joint (46). However, a recent study suggested that any Th17 cells that are able to traffic to the joints (regardless of antigen specificity) can induce arthritis development by acting as a local source of IL-17, and that direct recognition of joint antigens may not be required for arthritis to develop in such a setting (47). In this case, then, the key role of the 6.5 TCR in disease development could be in establishing conditions that favor Th17 cell formation; these could include the lymphopenic environment that develops in young TS1×HACII mice as a consequence of severe thymocyte deletion (22), since lymphopenic environments have been found to contribute to Th17 cell formation in the SKG model of arthritis (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be elucidated whether infection is a cause or a consequence (or neither) of the numerous immune aberrations displayed by RA patients. Do infections play a pathogenic role by evoking immune reactions, for example resulting from molecular mimicry with a specific microbe or from repeated exposures to a multitude of foreign agents triggering a wear and tear type of immune defence?8…”
Section: Introductionmentioning
confidence: 99%